Corticotropin Releasing Factor Binding Protein as a Novel Target to Restore Brain Homeostasis: Lessons Learned From Alcohol Use Disorder Research - Curley, Dallece E.; Webb, Ashley E.; Sheffler, Douglas J.; Haass-Koffler, Carolina L. (Frontiers in Behavioral Neuroscience, 2021)
Stress is well-known to contribute to the development of many psychiatric illnesses including alcohol and substance use disorder (AUD and SUD). The deleterious effects of stress have also been implicated in the acceleration of biological age, and age-related neurodegenerative disease. The physio-pathology of stress is regulated by the corticotropin-releasing factor (CRF) system, the upstream component of the hypothalamic-pituitary-adrenal (HPA) axis. Extensive literature has shown that dysregulation of the CRF neuroendocrine system contributes to escalation of alcohol consumption and, similarly, chronic alcohol consumption contributes to disruption of the stress system. The CRF system also represents the central switchboard for regulating homeostasis, and more recent studies have found that stress and aberrations in the CRF pathway are implicated in accelerated aging and age-related neurodegenerative disease. Corticotropin releasing factor binding protein (CRFBP) is a secreted glycoprotein distributed in peripheral tissues and in specific brain regions. It neutralizes the effects of CRF by sequestering free CRF, but may also possess excitatory function by interacting with CRF receptors. CRFBP’s dual role in influencing CRF bioavailability and CRF receptor signaling has been shown to have a major part in the HPA axis response. Therefore, CRFBP may represent a valuable target to treat stress-related illness, including: development of novel medications to treat AUD and restore homeostasis in the aging brain. This narrative review focuses on molecular mechanisms related to the role of CRFBP in the progression of addictive and psychiatric disorders, biological aging and age-related neurodegenerative disease. We provide an overview of recent studies investigating modulation of this pathway as a potential therapeutic target for AUD and age-related neurodegenerative disease.